2018
DOI: 10.5812/pedinfect.60288
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Genotyping of Viral Gastroenteritis in Hospitalized Children Below Five Years Old in Cairo, Egypt

Abstract: This work aimed to study the detection and genotyping of rotavirus, enteric adenovirus, and astrovirus in Egyptian hospitalized children below five years old, associated with non-bacterial diarrhea. In total, 119 fecal samples were obtained from the target population, admitted to Abu El-reesh hospital in Cairo, Egypt. Based on the findings, the detection rate of at least one viral infection was 36.7% in children below five years old, whereas, the overall detection rate of rotavirus, adenovirus, and coinfection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
24
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(45 citation statements)
references
References 19 publications
18
24
1
Order By: Relevance
“…Our findings for rotavirus were relatively similar to the previous reports conducted in Egypt (8.3%), South Africa (14.9) and Brazil (15.7%) (Rizk and Allayeh, 2018;Chigor and Okoh, 2012;Miagostovich et al, 2014) and disagree with the previously reports conducted globally in drinking water samples such as; China (22.4%), Ghana (48%), and Italy (37.5%) (Glass et al, 1996;Sumi et al, 2013;Grassi et al, 2010). As well our results for enteric adenovirus were very low in contrast with the previous studies conducted in sewage (10.4%) and stool samples (6.7%) collected from Egypt according to previous studies (Kamel et al, 2010;Allayeh et al, 2018) and globally as West Africa (12.9%) (Verheyen et al, 2009). These comprehensive data for identification the prevalence of different pathogens in waters from several governorates in Egypt indicated the low prevalence of viral contamination in contrast with Acanthamoeba contamination.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our findings for rotavirus were relatively similar to the previous reports conducted in Egypt (8.3%), South Africa (14.9) and Brazil (15.7%) (Rizk and Allayeh, 2018;Chigor and Okoh, 2012;Miagostovich et al, 2014) and disagree with the previously reports conducted globally in drinking water samples such as; China (22.4%), Ghana (48%), and Italy (37.5%) (Glass et al, 1996;Sumi et al, 2013;Grassi et al, 2010). As well our results for enteric adenovirus were very low in contrast with the previous studies conducted in sewage (10.4%) and stool samples (6.7%) collected from Egypt according to previous studies (Kamel et al, 2010;Allayeh et al, 2018) and globally as West Africa (12.9%) (Verheyen et al, 2009). These comprehensive data for identification the prevalence of different pathogens in waters from several governorates in Egypt indicated the low prevalence of viral contamination in contrast with Acanthamoeba contamination.…”
Section: Discussioncontrasting
confidence: 99%
“…The present study indicated the wet seasons (winter and autumn) were the peak for rotavirus and adenovirus. This result was similar with the previous report conducted in Egypt about the incidence of both rotavirus and adenovirus (Allayeh et al, 2018).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This result corresponds to the researcher's results, Allayeh et al [27] and this is in line with the results of many studies conducted inside Iraq and outside it, which confirms that the female infection rate is higher than the male infection rate. Temu et al [30] indicated that the female infection rate is 23%, which is slightly higher than the male infection rate which reached 19%.…”
Section: Table (1): Distribution Of Enteric Virus's Infection Betweensupporting
confidence: 92%
“…This result coincided with the result of the researcher, AL-Jeboury [26] in Babylon Governorate, where the highest incidence of intestinal viruses was recorded among children aged (2-3 years). It also coincided with the results of the researcher ,Allayeh et al [27] in Egypt, who found in their results that the highest incidence of viral intestinal infection in relation to (Rota, Astro and Adenovirus) was in the age group of less than one year, as well as consistent with the results of the researcher in Thi Qar, where the highest incidence of injury in the age group was less than two years, which was estimated at (60%) [28].…”
Section: Table (1): Distribution Of Enteric Virus's Infection Betweensupporting
confidence: 91%